Studies On Amoebicides At The Child Health Department Dr. Pirngadi Hospital, Medan (1969 - 1979) - Sondang Tambunan; Chairuddin P. Lubis; Helena Siregar (Paediatrica Indonesiana, 1984)
Since 1969-1979 trials with amoebicides had been done 9 times in OPD of the Child Health Department, Dr. Pirngadi Hospital, Medan. The children were treated ambulatorily. The tablets were administered under close supervision at the subdivision of Gastroenterology for 3 consecutive days. Stools examination had been done, with direct faecal film only, every day for the first 4 days and once a week for 3 weeks. Evaluation was done by assessing the parasitological and clinical cure rate. A clinical trial with metronidazole had been conducted in 3 groups of children. Each of the three groups consisted of 50 children, and were treated ambulatorily with a single daily dose for three days.The first group treated with a dose of 50 mg/kg bw/day had in a cure rate of 89% and 100%, the second group with a dose of 25 mg/kg bw/day 87% and 85%. The third group also with a dose of 25 mg/kg bw/day showed cure rate of 93% and 91%. These differences of results in group I, II and III proved to be not statistically significam. There were no side effects observed.Tinidazole and omidazole were indeed very effective for treating intestinal amoebiasis, the cure rate was 100%, and no side effects observed.